Autism as a disorder of affective empathy - Schnitzler, Tim; Fuchs, Thomas (Psychopathology, 2024)
Since the first description by Leo Kanner, individuals with autism spectrum disorder (ASD) have been attributed a reduced empathy. However, it has not yet been clarified how empathy is specifically impaired in autism. Typically, scholars distinguish between the affective and the cognitive dimensions of empathy. The latter largely overlaps with the concept of the theory of mind (ToM), according to which we need internal inferences or simulations for gaining access to the hidden mental states of others. Since a deficit in ToM is a widely accepted explanation for difficulties of individuals with ASD in social interactions, limitations in cognitive empathy are accordingly assumed. Regarding affective empathy, there are contradictory results using various methods, showing an impaired affective empathy. The main aim of the paper is to present ASD primarily as a disorder of shared interpersonal and interaffective experiences and thus of affective empathy by means of a phenomenological analysis considering empirical studies. In this framework, a deficit of the ToM is accepted but criticized as a central explanatory approach for ASD since (1) it assumes a fundamental inaccessibility of other people, which does not correspond to our everyday social situations, and (2) it manifests developmentally long after the first signs of ASD, which means that its deficit cannot explain the basic autistic difficulties in social interactions.
Online veröffentlicht: 18. Oktober 2023
Gesehen am 24.05.2024